PENGARUH SUMBER DAYA MANUSIA TERHADAP PERTUMBUHAN EKONOMI PROVINSI KEPULAUAN BANGKA BELITUNG SEBELUM DAN DITENGAH PANDEMI COVID-19 FIXED EFFECT MODEL (FEM) - Abdul Ghoni (LPPM STIE PERTIBA Pangkalpinang, 2022)
This study aims to analyze the relationship of determination between human resources and economic growth in the Province of the Bangka Belitung Islands before and in the midst of the COVID-19 pandemic, using the Fixed Effect Model (FEM) approach. The results of the study indicate that the human resource variable has a positive and significant coefficient value on economic growth, this indicates that the higher Human Resources (IPM) will significantly affect the rate of economic growth (GRDP) in the province of the islands of Bangka Belitung.